Curso de quadros: formação de professores e instrutores pelo/para o SENAI - São Paulo (1942-1955) - Zucchi, Bianca Barbagallo (2012)
This current research aims at investigating the teacher s and instructor s graduation course provided by National Service of Industrial Training (Senai), located in São Paulo, and its Quadros Course from 1946 on. Through school teaching, Senai intended to graduate blue-collar workers based on rational teaching methods which proposed, among other changes, that the Professional Teaching be taught by instructors and teachers who have not only knowledge about a specific job position or industry, but also theoretical and practical knowledge related to the rational principles supported by this institution. In order to achieve this aim, Senai has designed the Quadros Course which aimed two different outcomes. In the one hand, it aimed at introducing this institution s teachers who had been graduated in Normal Schools into the factory environment and into rational methods. On the other hand, it aimed at ensuring that the instructors who came from the plants were graduated as rational educators. Textbooks made by teachers and/or instructors were analyzed as well as other documentation developed by Senai. The focus of the analysis was developed under 3 thematic axes: a) The legitimacy and appropriation that Senai and its Quadros course had established with the New School Movement; b)The way the Quadros Course s authors understood and represented adolescence and teenage workers who studied at the this institution; c) Which practical instructions the authors gave to teachers and instructors. The theoretical bases used for this analysis were: the school form concept (Vicent, Lahire, Thin, 2001); the artifice and specialized work concept by Sennett (2009); the analysis transnational perspective (López, 2012; Bayly et. al., 2006; Seigel, 2009; Salvatore, 1998) and the appropriation concept by Chartier (1988)